2018
DOI: 10.3390/jrfm11030035
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Risk Management Practices and Firm Performance, the Mediating Role of Competitive Advantage and the Moderating Role of Financial Literacy

Abstract: In the current turbulent market, firms spend lots of tangible and intangible resources to gain competitive advantage and superior performance. Prior studies have discussed several determinants of competitive advantage and performance, particularly in developed economies, whereas small-and medium-sized enterprises (SMEs) in emerging economies have received minor attention. This study examines the mediating role of competitive advantage between enterprise risk management practices and SME performance and the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 55 publications
10
105
1
10
Order By: Relevance
“…Our findings indicate a significant positive influence of SCP on firm performance which supported H5 of the study. Our findings are consistent with Yang, Ishtiaq and Anwar [7] who scrutinized that a firm competitive position can boost its performance in the turbulent market. As claimed by Schrettle et al [48], a sustainable position or sustainability is deemed a significant driver to enhance a firm performance in future both in developed and developing economies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings indicate a significant positive influence of SCP on firm performance which supported H5 of the study. Our findings are consistent with Yang, Ishtiaq and Anwar [7] who scrutinized that a firm competitive position can boost its performance in the turbulent market. As claimed by Schrettle et al [48], a sustainable position or sustainability is deemed a significant driver to enhance a firm performance in future both in developed and developing economies.…”
Section: Discussionsupporting
confidence: 92%
“…More preciously, Porter [33] suggests that a firm can gain cost based sustainable competitive position by reducing different types of costs related to material, operation, management and adverts as well as can gain differentiation based sustainable competitive position by offering unique products and services which may not be offered by competitors. Studies, from this perspective, have concluded that both cost-based and differentiation based competitive advantage/position can improve profitability and performance of firms Lechner and Gudmundsson [5,7,34]. Therefore; Hypothesis 5 (H5).…”
Section: Sustainable Competitive Position and Firm Performancementioning
confidence: 93%
See 2 more Smart Citations
“…Authors constructed new 3D Enterprise Risk Model (ERM) that is a suitable risk management tool for assessing and predicting the risk impact on the enterprise performance. As reported byYang, Ishtiaq, Anwar (2018), ERM has a significant influence on competitive advantage and increase of performance Kiseľáková, Horváthová, Šofranková, Šoltés (2015). conclude that the most significant impact on performance of the enterprises has just financial risk.…”
mentioning
confidence: 83%